In Sickness and in Health: How HRM Influences Employee Well-Being and Presenteeism - Ferreira, A.I.; Duarte, H. (3rd Meeting of the International Attendance Behaviour Network: Understanding Attendance Behaviour in Context, Place, and Time, 2025)
This presentation explores the intricate relationship between Human Resource Management (HRM) practices, employee well-being, and presenteeism. Drawing on a comprehensive study of Portuguese companies, we delve into how high-performance work systems, compensation, and organizational identity collectively shape employee outcomes. Our findings offer crucial insights for both academic researchers and HR professionals seeking to foster healthier and more productive work environments.